Diadromous fish run assessment: a double-observer model using acoustic cameras to correct imperfect detection and improve population abundance estimates - Boulenger, Clarisse; Roussel, Jean-Marc; Beaulaton, Laurent; Martignac, François; Nevoux, Marie (Frontiers in Ecology and Evolution, 2024)
Diadromous fish populations have strongly declined over decades and many species are protected through national and international regulations. They account for less than 1% of fish biodiversity worldwide, but they are one of the most perceptible linkage between freshwater and marine ecosystems. During their migration back and forth, diadromous fish species are subjected to many anthropogenic threats, among which river damming can severely limit access to vital freshwater habitats and jeopardize population sustainability. Here, we developed a method based on a double-observer modelling approach for estimating the abundance of diadromous fish during their migration in rivers. The method relies on two independent and synchronous records of fish counts that are analysed jointly thanks to a hierarchical Bayesian model to estimate detection efficiencies and daily fish passage. We used simulated data to test model robustness and identify conditions under which the developed approach can be used. The approach was then applied to empirical data to estimate the annual silver eel run in the Touques River, France. The analysis of simulated datasets and of the study case gives evidence that the model can provide robust, accurate and precise estimates of detection probabilities and total fish abundance, in a set of conditions dependent on the information provided in the data (annual distribution of fish passage, annual number of observation, pairing period, etc). Then, the method can be applied to various species and counting systems, including nomad acoustic camera devices. We discuss its relevance for programs on river continuity restoration, notably to quantify population restoration associated with dam removals.